Effect of Hydrogen Peroxide and Vinegar Compound on the Optical Behavior of Heat Cure Denture Resins - Farnaz Firouz; Saeed Nikanjam; Armaghan Shahbazi; Zahra Cheraghi; Hadiseh Torabi (پزشکی بالینی ابن سینا, 2022)
Background and Objective: Denture cleansing and disinfecting techniques include mechanical brushing and using ultrasonic units, as well as microwave radiation, in conjunction with various chemical cleansers. The present study investigated the effect of different ratios of vinegar and hydrogen peroxide on the color changes of hard heat acrylic resins. Materials and Methods: This experimental study was conducted on 40 specimens with 3×20×20 mm dimensions. Samples were divided into four groups: one control group and three experimental groups with a combination of two types of hydrogen peroxide and vinegar with ratios of 1:1, 3:1, and 3:1. Samples were immersed in disinfectant solution for 8 h every day for one month. Afterward, they were subjected to spectrophotometry to evaluate their color properties based on a, b, and L color parameters. The color changes of each sample were then calculated using the ΔE00 and ΔW ID parameters. Data were analyzed using ANOVA and Tukey HSD tests at a significance level of 0.05. Results: The mean and standard deviation of ΔE00 parameter in vinegar and hydrogen peroxide groups with 3:1, 1:1, and 1:3 ratios, and the control were equal to 0.75±0.1, 0.5±0.2, 1.57±0.2, and 0.03±0.01, respectively. The mean and standard deviation of ΔW ID parameter in vinegar and hydrogen peroxide groups with 3:1, 1:1, and 1:3 ratios, and the control group were 0.7±0.96, 0.48±0.12, 1.51±0.47, and 0.09±0.07, respectively. Conclusion: The highest color change and bleaching of base denture resin occurred in the group with the 3:1 ratio of hydrogen peroxide to the vinegar, which was significantly different from other groups (P<0.001) and also higher than the perceptibility threshold.